An Analysis of Students’ Error in Writing Application Letter at XII Grade in SMK 1 Ranah Batahan - Annisa Silvia; Arifmiboy; Meylanmelani; Veni Roza (Journal of Educational Management and Strategy, 2022)
There were student problem foun at SMKN 1 Ranah Batahan which consist of  TP, TAV, TKJ and OTKP. Some students errors commited in misformation and some others did errors in format application lette. This research used a descriptive quantitative. The populations of this research were 105 of  XII Grade students of SMKN 1 Ranah Batahan which consist of  TP, TAV, TKJ and OTKP. The researcher used  purposive sampling to determine because the researcher has some consideration to determine the samples. The researcher chose one of fourth classes as the sample. The sample in this research was 24 students. The tehnique of the data collection in this research was students worksheet of writing application letter. To analyze the data collected the researcher  used steps by Ellis in journal Rizki Ananda namely selection, identification, classify and to calculate the data using the formula by sugiono namely: P=f/Nx 100%. The result of the research showed  that students’ error in writing application letter at XII grade in SMKN 1 Ranah Batahan were 149.4 errors. First, there were 62 errors in misformation which were 41% of total errors. Second, there were 50.2 errors in omission which were 34% of total errors. Third there were 26.3 error in addition which were 18% of total errors. There were errors 10.9 errors  in misordering which were 7% of total errors. Furtheremore, the dominant errors in this research was missformation which were 41% of total errors. Abstrak Terdapat permasalahan siswa yang ditemukan di SMKN 1 Ranah Batahan yang terdiri dari TP, TAV, TKJ dan OTKP. Beberapa siswa melakukan kesalahan dalam salah informasi dan beberapa lainnya melakukan kesalahan dalam format surat lamaran Penelitian ini menggunakan deskriptif kuantitatif. Populasi penelitian ini adalah 105 siswa kelas XII SMKN 1 Ranah Batahan yang terdiri dari TP, TAV, TKJ dan OTKP. Peneliti menggunakan purposive sampling dalam penentuannya karena peneliti mempunyai beberapa pertimbangan untuk menentukan sampel. Peneliti memilih salah satu dari keempat kelas sebagai sampel. Sampel dalam penelitian ini adalah 24 siswa. Teknik pengumpulan data dalam penelitian ini adalah lembar kerja siswa menulis surat lamaran. Untuk menganalisis data yang terkumpul peneliti menggunakan langkah-langkah Ellis dalam jurnal Rizki Ananda yaitu memilih, mengidentifikasi, mengklasifikasikan dan menghitung data menggunakan rumus menurut sugiono yaitu: P=f/Nx 100%. Hasil penelitian menunjukkan kesalahan penulisan surat lamaran kerja siswa kelas XII SMKN 1 Ranah Batahan sebanyak 149,4 kesalahan. Pertama, terdapat 62 kesalahan dalam misformation yang merupakan 41% dari total kesalahan. Kedua, ada 50,2 kesalahan dalam penghilangan yang merupakan 34% dari total kesalahan. Ketiga ada 26,3 kesalahan tambahan yang merupakan 18% dari total kesalahan. Ada kesalahan 10,9 kesalahan dalam kesalahan pemesanan yang merupakan 7% dari total kesalahan. Selain itu, kesalahan yang dominan dalam penelitian ini adalah kesalahan formasi sebesar 41% dari total kesalahan.